Plasmid-associated adherence of Shigella flexneri in a HeLa cell model. - Pál, T (1989)
The initial interaction of Shigella flexneri with HeLa cells was studied at 4 degrees C, a temperature that inhibits parasite-directed endocytosis. It was found that invasive strains were 10-fold more adherent to HeLa cells than were isogenic, noninvasive strains which had lost a 140-megadalton plasmid. Adherent strains were also more hydrophobic than were nonadherent strains.